Implementasi Model Pembelajaran Berbasis Project Based Learning (Pjbl) Untuk Meningkatkan Keterampilan Problem Solving - Ahmad, Zohiri; Fahrurrozi, Fahrurrozi; Juaini, Muhammad (Universitas Hamzanwadi, 2026)
This study examines the implementation of Project Based Learning (PjBL) based on the local wisdom “Begawe Beleq” to improve problem-solving skills of ninth-grade students at MTs. Mu’allimat NWDI Pancor, East Lombok. Using a descriptive qualitative approach with data collection techniques including observation, interviews, and document study, the study found that 85% of students showed significant improvement in problem analysis skills, 90% were able to relate local values to cleanliness issues, and 80% demonstrated progress in collaboration and communication. The PjBL model based on local wisdom is effective not only in developing problem solving but also 21st-century skills such as critical thinking and creativity, while helping internalize cultural values and character. Teachers act as facilitators, guiding meaningful learning processes, making this model a valuable contribution to developing contextual learning relevant to local culture, and recommending the development of thematic modules based on local wisdom to enhance the quality of education in Indonesia.